Disorders of Blood Pressure Regulation Phenotypes, Mechanisms, Therapeutic Options (Updates in Hypertension and Cardiovascular Protection, 2018)
This book aims to present a comprehensive classification of hypertensive phenotypes based on underlying target organ involvement. Particular emphasis is placed on review and assessment of clinical presentation, pathophysiologic mechanisms, and possible specific therapeutic options for each hypertension phenotype. Several of these phenotypes are well known and well described in the literature, such as prehypertension, white coat and masked hypertension, isolated systolic hypertension, renovascular hypertension, endocrine hypertension, pediatric hypertension, and gestational hypertension. Other hypertension phenotypes, however, are not widely recognized, being reported only in special reviews; examples include hypertension associated with renal calculus disease and other rarer causes such as Turner syndrome, herbal and medicinal compounds, and pharmacologic agents. A detailed account of the various causes of monogenic hypertension is also included. Finally, a section is devoted to general aspects of hypertension, including the significance of blood pressure indices, the natural course of untreated and treated hypertension, hypertension mechanisms, genetics, and guidelines for blood pressure control. .